Invasive micropapillary carcinoma of the male breast: Case report and review of the literature. (2015) - Stranix, J.T.; Kwa, M.J.; Shapiro, R.L.; Speyer, J.L.
Abstract: Background: Invasive micropapillary carcinoma (IMPC) of the breast is a rare and aggressive variant of invasive ductal carcinoma. IMPC has been reported to account for 3–6% of all breast cancers, and these tumors have been associated with a strong tendency to invade lymphatics with early spread to regional lymph nodes. Patients and methods: We present a case of this rare type of breast cancer diagnosed in a male patient and summarize the current literature to date. Results: Review of the literature on invasive micropapillary breast carcinoma revealed 27 retrospective cohort studies and case series. Significant heterogeneity of inclusion criteria and follow up data prevented meta-analysis. Tumors with an IMPC component demonstrated an early and high rate of lymphatic metastasis compared to invasive ductal carcinoma, however, no significant association was found between IMPC and decreased overall survival. Conclusions: The IMPC data currently available indicates a strong trend towards a higher initial stage at diagnosis and possibly an increased risk of loco-regional recurrence, but remains underpowered to elucidate the prognostic effect of IMPC phenotype on survival. Further studies are warranted to establish the potential of this unique histologic phenotype to serve as a prognostic indicator and guide tumor-specific oncologic therapy.